2011
DOI: 10.1098/rspb.2011.0343
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing the dynamics of ancient human populations from radiocarbon dates: 10 000 years of population growth in Australia

Abstract: Measuring trends in the size of prehistoric populations is fundamental to our understanding of the demography of ancient people and their responses to environmental change. Archaeologists commonly use the temporal distribution of radiocarbon dates to reconstruct population trends, but this can give a false picture of population growth because of the loss of evidence from older sites. We demonstrate a method for quantifying this bias, and we use it to test for population growth through the Holocene of Australia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 30 publications
4
48
0
Order By: Relevance
“…Fig. 3 shows measurements of the annual growth rate calculated from SPDs for North America (26), Australia (27), and Europe (28). The SPD comparison is restricted to studies that report measurements of the long-term growth rate.…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…Fig. 3 shows measurements of the annual growth rate calculated from SPDs for North America (26), Australia (27), and Europe (28). The SPD comparison is restricted to studies that report measurements of the long-term growth rate.…”
Section: Significancementioning
confidence: 99%
“…The growth rate calculated from these data are significant because the methodology used to estimate the population size is completely independent from our analysis and therefore provides an important cross-check on the systematic uncertainties of the SPD approach. Many studies have indicated that SPDs are valid demographic proxies (25)(26)(27)(28)(29)(30)33). Fig.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Time-series radiocarbon data is widely used as a proxy for human activity or prehistoric population [13,17,25,[31][32][33][34]. Analysis and interpretation of this form of data is complex and has several limitations ([24]; see the electronic supplementary material).…”
Section: Key Assumptionsmentioning
confidence: 99%
“…Observations from the field Archaeological and paleoecological evidence already confirm that humans have a long history of altering ecosystems at sites around the world beginning in the late Pleistocene (Smith and Zeder, 2013;Braje and Erlandson, 2013;Ellis et al, 2013). Site data are also being used to reconstruct population and land use histories at increasingly larger scales and levels of detail Johnson and Brook, 2011;Gaillard et al, 2010;Dincauze, 2000;Shennan et al, 2013). Nevertheless, it is clear that land-use histories and impacts of regional environments varied greatly across contemporaneous regions, which calls for more detailed local and regional studies and methods of integrating them across global scales.…”
Section: Introductionmentioning
confidence: 99%